Flame retardance-donated lignocellulose nanofibers (LCNFs) by the Mannich reaction with (amino-1, 3, 5-triazinyl)phosphoramidates and their properties. Issue 6 (26th January 2022) - Ono, Fumiaki; Okihara, Takumi; Osaka, Noboru; Nagaoka, Noriyuki; Kameoka, Yuji; Ishikawa, Akira; Ooki, Hironari; Ito, Takumi; Todome, Daisuke; Uemoto, Shinya; Furutani, Mitsuaki; Inokuchi, Tsutomu; et al.
Abstract : LCNFs were grafted with nitrogen/phosphorus-containing melamines to achieve potent flame-retardance and converted to PP-composites of improved mechanical properties. Abstract : Nitrogen/phosphorus-containing melamines (NPCM), a durable flame-retardant, were prepared by the successive treatment of ArOH (Ar = Br n C6 H5− n, n = 0, 1, 2, and 3) with POCl3 and melamine monomer. The prepared flame-retardants were grafted through the CH2 unit to lignocellulose nanofibers (LCNFs) by the Mannich reaction. The resulting three-component products were characterized using FT-IR (ATR) and EA. The thermal behavior of the NPCM-treated LCNF fabric samples was determined using TGA and DSC analyses, and their flammability resistances were evaluated by measuring their Limited Oxygen Index (LOI) and the UL-94V test. A multitude of flame retardant elements in the fabric samples increased the LOI values as much as 45 from 20 of the untreated LCNFs. Moreover, the morphology of both the NPCM-treated LCNFs and their burnt fabrics was studied with a scanning electron microscope (SEM). The heat release lowering effect of the LCNF fabric against the water-based paint was observed with a cone calorimeter. Furthermore, the mechanical properties represented as the tensile strength of the NPCM-treated LCNF fabrics revealed that the increase of the NPCM content in the PP-composites led to an increased bending strength with enhancing the flame-retardance.